Postawy wobec pracy - Sarapata, Adam (Wydział Prawa i Administracji UAM, 1988)
The author confronts the opinion — voiced generally by the management circles and by a considerable part of the society — that Poles do not set a high value on work and that they are responsible for their negative attitude towards work with his own research the results of which prove that: 1) in the value system of Poles work takes an important place; 2) the attitude of the majority towards work is determined by conditions which do not depend on employees but on the management, on the management's intellectual, moral and organizational qualities.
Attitudes towards work